Ceramic Bracket Debonding: The Evaluation of Two Debonding Techniques and their Effect on Enamel - Amditis Constantine (Sciendo, 1994)
Enamel fractures have been associated with the debonding of some ceramic brackets which have a chemical bond to the enamel. The purpose of this study was to assess the enamel surface subsequent to debonding Transcend * series 2000 * ceramic brackets using two debonding techniques. One hundred extracted human premolars were divided randomly into groups of two and prepared for bonding. Group I teeth had brackets bonded with Transbond* light-cured adhensive and Group 2 teeth had brackets bonded with Unile* chemically-cured adhensive. Bonded teeth were stored in normal saline at 37°C for 5 days and thermocycled. Teeth in both groups were subdivided randomly into Subgroups A and B. Teeth in Subgroup A had brackets debonded with the Transcend debonding instrument while teeth in Subgroup B had brackets debonded with ligature cutters. Each tooth was examined under light microscopy and those teeth suspected of enamel fracture were assessed by scanning electron microscopy.